2021
DOI: 10.3390/microorganisms9020370
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Microbiome Analysis in a Dextran Sulfate Sodium-Induced Colitis Mouse Model

Abstract: The role of the gut microbiota in the pathogenesis of inflammatory bowel disease (IBD) has been in focus for decades. Although metagenomic observations in patients/animal colitis models have been attempted, the microbiome results were still indefinite and broad taxonomic presumptions were made due to the cross-sectional studies. Herein, we conducted a longitudinal microbiome analysis in a dextran sulfate sodium (DSS)-induced colitis mouse model with a two-factor design based on serial DSS dose (0, 1, 2, and 3%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 85 publications
3
22
2
Order By: Relevance
“…DSS could decrease the abundance of Bacteroidetes and increase the abundance of Firmicutes , while Dou et al [ 33 ] found that DSS could increase the abundance of Bacteroidetes . Park et al [ 34 ] concluded that the alteration of the composition of the gut microbiota by different concentrations of DSS was highly variable. This likely explains why this experimental data differed from previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…DSS could decrease the abundance of Bacteroidetes and increase the abundance of Firmicutes , while Dou et al [ 33 ] found that DSS could increase the abundance of Bacteroidetes . Park et al [ 34 ] concluded that the alteration of the composition of the gut microbiota by different concentrations of DSS was highly variable. This likely explains why this experimental data differed from previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although Axl has been known to act as a negative regulator in the pathogenesis of IBD 18 , to the best of our knowledge, the effect of Axl on changes in the composition of the gut microbiota has not been investigated to date. Previous studies have demonstrated that IBD patients show a reduced abundance of the genera Bacteroides 65 , 66 , Alloprevotella 67 , Odoribacter 68 , Bifidobacterium , Eggerthella 69 , and Olsenella but an increased in Escherichia , Shigella , and Actinobacillus 70 . In addition, the species such as B. vulgatus , B. caccae , B. bifidum , and B. longum 68 are decreased in patients with IBD, whereas the species S. enterica 71 , E. coli 67 , A. segnis , H. parainfluenzae , and E. corrodens 68 are enhanced.…”
Section: Discussionmentioning
confidence: 96%
“…Another potential source of differential effects lies with the effects upon the gut microbiome, because different forms of BG might differently affect the gut microbiome composition [ 69 , 70 ]. While no differences in the healthy mice with BG (without DSS), Pachyman + DSS demonstrated the lowest beneficial Firmicute bacteria [ 40 , 71 ], and WGP + DSS produced the lowest Bacteroidetes [ 40 , 72 , 73 ], and Oat-BG + DSS did not alter the fecal microbiome. These subtle differences of bacterial abundance between BG + DSS vs. DSS alone were accompanied by a similar taxonomic diversity among these groups, which were supported by the ex vivo incubation of mouse feces with different BGs.…”
Section: Discussionmentioning
confidence: 99%